Herpes zoster ophthalmicus presenting as orbital abscess along with superior orbital fissure syndrome: A case report - Poonam Lavaju; Badri Prasad Badhu; Sangeeta Shah (Indian Journal of Ophthalmology, 2015)
Orbital abscess and superior orbital fissure syndrome (SOFS) are rare manifestations of herpes zoster ophthalmicus. Herein, we report a case of orbital abscess along with SOFS in a 2.5-year-old-male child secondary to herpes zoster infection. He presented with a 5-day history of proptosis and ptosis of the right eye that had been preceded by vesicular eruptions on the right forehead and scalp. Computed tomography scan of the head and orbit showed orbital abscess and right cavernous sinus thrombosis. A diagnosis of orbital abscess with SOFS secondary to herpes infection was made. The condition subsequently improved following antiviral therapy, intravenous vancomycin and amikacin, and oral corticosteroids.